2017
DOI: 10.1080/15481603.2017.1309125
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity analysis and accuracy assessment of the land transformation model using cellular automata

Abstract: This study evaluates the effects of cellular automata (CA) with different neighborhood sizes on the predictive performance of the Land Transformation Model (LTM). Landsat images were used to extract urban footprints and the driving forces behind urban growth seen for the metropolitan areas of Tehran and Isfahan in Iran. LTM, which uses a back-propagation neural network, was applied to investigate the relationships between urban growth and the associated drivers, and to create the transition probability map. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(15 citation statements)
references
References 54 publications
(73 reference statements)
0
14
0
1
Order By: Relevance
“…To know urban growth there are several approaches to study such as population, soil surveys, air surveys, water surveys, remote sensing, and urbanization [16]. Remote sensing in GIS is highly accurate and efficient in assessing urban growth [17]. Along with increasingly sophisticated technological advances especially in technological developments in the field, in use detailed temporal and spatial data on the geographic information system and remote sensing directly lead to an increasing number of model development for land use especially in urban growth [4,8].…”
Section: Urban Growth Modelmentioning
confidence: 99%
“…To know urban growth there are several approaches to study such as population, soil surveys, air surveys, water surveys, remote sensing, and urbanization [16]. Remote sensing in GIS is highly accurate and efficient in assessing urban growth [17]. Along with increasingly sophisticated technological advances especially in technological developments in the field, in use detailed temporal and spatial data on the geographic information system and remote sensing directly lead to an increasing number of model development for land use especially in urban growth [4,8].…”
Section: Urban Growth Modelmentioning
confidence: 99%
“…LTM uses ANN, which is a machine learning technique, for modelling land cover change [37,[39][40][41]. The multilayer perceptron is one of the well-known ANN forms that is most commonly employed in land cover change science [1].…”
Section: Land Transformation Modelmentioning
confidence: 99%
“…First, the ANN initially assigns random values to ANN parameters (weights and biases), then the multilayer perceptron applies random weights and biases to the input data in order to estimate the outputs. Second, the ANN calculates the mean squared error (difference between the estimated outputs and reference outputs), which is then propagated backward to the previous layers [40]. Optimum model parameters values are estimated by iterating the LTM model through many cycles.…”
Section: Land Transformation Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Shafizadeh-Moghadam et al and Zheng et al evaluated the effect of cell neighborhood size on the accuracy of CA simulation by selecting two cities in Iran, Tehran and Isfahan, as the research areas. Through PA (product accuracy), OA (overall accuracy), and FoM (the figure of merit), the accuracy of the simulation under the scales of 3 m × 3 m, 5 m × 5 m, 7 m × 7 m, and 9 m × 9 m was verified, and the results showed that the best simulation was achieved under the scale of 7 m × 7 m [57,58]. Therefore, in order to determine the reliability of CA, the selection of cell neighborhood size must be verified.…”
Section: Introductionmentioning
confidence: 99%